The relationship between lower-limb explosive strength and climbing speed in elite speed climbers: A comprehensive analysis based on muscle morphology and electromyography - Li, M.; Zhu, Y.; Peng, Y. (International Journal of Sports Physiology and Performance, 2026)
Purpose: This study evaluated how lower-limb explosive strength relates to 15-m speed-climbing performance by combining jump kinetics, muscle morphology, and surface electromyography (sEMG).